Coupled molybdenum and iron isotopes distinguish seawater and hydrothermal inputs to seep carbonates - Hangyu Nan; Xiaoming Miao; Hongxiang Guan; Ang Li; Zhilei Sun; Thomas J. Algeo; Davide Oppo; Nengyou Wu; Sanzhong Li (Geochimica et Cosmochimica Acta, 2026)

Strategies for cell-based meat production based on 3D-printed scaffolds - Yuan Wang; Ang Jin; Renwick Dobson; Olaf Diegel; Jenny Malmström; Laura J. Domigan (Critical Reviews in Food Science and Nutrition, 2026)

Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

Making Restoration Effective for Dynamic Coastal Wetlands - Qiang He; Zu'ang Li; Chris S. Elphick; Yizhou Sun; William J. Sutherland; Nigel G. Taylor; Kerstin Wasson (Global Change Biology, 2025)
To halt and reverse the trends of ecosystem loss and degradation under global change, nations globally are promoting ecosystem restoration. Restoration is particularly crucial to coastal wetlands (including tidal marshes, mangrove forests, and tidal flats), which are among the most important ecosystems on Earth but have been severely depleted and degraded. In this review, we explore the question of how to make restoration more effective for coastal wetlands in light of the often‐overlooked dynamic nature of these transitional ecosystems between land and ocean. Currently, restoration efforts have focused on removing anthropogenic threats, habitat reconstruction, and planting foundation species, often with mixed success and high costs. The challenges largely lie in the abiotic and biotic dynamics of these transitional ecosystems, including (i) fluctuating environmental stresses, (ii) variable trophic and nontrophic species interactions, (iii) changing connectivity with adjacent land, sea, and freshwater systems, and (iv) accelerating climate change, including sea level rise, droughts, and storms. Future restoration should explicitly account for these abiotic and biotic dynamics from threat removal to habitat reconstruction, assisted succession, and post‐restoration management. We highlight novel yet practical measures to enhance success. In the coming decades, bending the curve of coastal wetland loss and degradation globally also requires better understanding of the abiotic and biotic dynamics of these transitional ecosystems prone to change, using this understanding to develop innovative restoration approaches, and applying new approaches to upscale restoration in synergy with socioeconomic development. Critical to these efforts are collaborations among ecologists, policymakers, business investors, restoration practitioners, and the many millions of people dependent on coastal wetlands.

The Emergence and Promise of Functional Chemogeography of Organic Matter - Ang Hu; James Stegen; Andrew J. Tanentzap; Jianjun Wang (Global Change Biology, 2025)
Organisms in ecosystems continuously release a myriad of organic matter molecules that undergo microbial and abiotic transformation, processes that critically influence carbon storage and climate feedbacks. Yet, a systematic understanding of what determines the transformation and persistence of organic matter across spatiotemporal scales remains elusive. We propose an emerging framework, termed “functional chemogeography,” to understand transformation and persistence of organic matter based on the chemical traits of molecules. This framework extends beyond a sole focus on intrinsic traits, which remain relatively constant across spatiotemporal scales, to emphasize extrinsic traits such as biochemical transformations and environmental responses, which vary spatiotemporally and are shaped by both intrinsic traits and the environment. When upscaled to the assemblage level using functional diversity indices, these extrinsic traits reveal a significant, and in some cases superior, capacity than intrinsic traits to explain biogeochemical processes, as demonstrated through a case study of dissolved organic matter in China's lakes. By integrating trait‐based perspectives into predictive models, this framework helps bridge chemical complexity with ecosystem biogeochemistry, thereby advancing our ability to predict the fate of global organic carbon under environmental change.

Holocene coral assemblages reveal similarities to living communities in Singapore's urban reef environment - Y.K. Samuel Chan; Ambert C.F. Ang; Min Choo; Ren Min Oh; Kyle M. Morgan; Peter A. Todd; Michael J. O'Leary; Danwei Huang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Investigating compliance with cow comfort and mastitis control recommendations on mastitis outcomes in smallholder dairy farms in Central Kenya - E.K. Ng'ang'a; J. VanLeeuwen; G.K. Gitau; S.L. McKenna; L.C. Heider; G.K. Keefe (Research in Veterinary Science, 2025)

Attributes of private yards along a rural-urban gradient in China highlight opportunities and limits to increase trees to benefit biodiversity and climate - Ang Zhang; Margaret J. Grose; Peter A. Vesk (Urban Ecosystems, 2025)

A web-based histology atlas for the freshwater sentinel species Daphnia magna - Mee S. Ngu; Daniel J. Vanselow; Carolyn R. Zaino; Alex Y. Lin; Jean E. Copper; Margaret J. Beaton; Luisa Orsini; John K. Colbourne; Keith C. Cheng; Khai C. Ang (Science of The Total Environment, 2025)

Residents and their trees: a quali-quantitative study of preferences, attitudes and social factors affecting trees planted in private yards in China - Ang Zhang; Peter A. Vesk; Margaret J. Grose (Trees, 2024)

Effects of Seed Tuber Size of Potato Varieties on Fungicide Spray Regime, Weed Infestation and Net Farm Income in Potato Production - J. M. Kilonzi; D. Githui; P. Pwaipwai; C. Kawira; S. Otieno; J. Kelele; N. Ng’ang’a; M. Nyongesa; J. Mafurah; A. Kibe (Potato Research, 2024)

Uncovering the magnitude of African pangolin poaching with extensive nanopore DNA genotyping of seized scales - Darren Yeo; Amy H. J. Chan; Kum Chew Hiong; Jasmine Ong; Jun Yuan Ng; Jie Min Lim; Wendy Zhang; Sara R. Lim; Charlene J. Fernandez; Anna M‐S. Wong; Benjamin P. Y‐H. Lee; Max D. Y. Khoo; et al. (Conservation Biology, 2024)
Trade in pangolins is illegal, and yet tons of their scales and products are seized at various ports. These large seizures are challenging to process and comprehensively genotype for upstream provenance tracing and species identification for prosecution. We implemented a scalable DNA barcoding pipeline in which rapid DNA extraction and MinION sequencing were used to genotype a substantial proportion of pangolin scales subsampled from 2 record shipments seized in Singapore in 2019 (37.5 t). We used reference sequences to match the scales to phylogeographical regions of origin. In total, we identified 2346 cytochrome b ( cytb ) barcodes of white‐bellied ( Phataginus tricuspis ) (from 1091 scales), black‐bellied ( Phataginus tetradactyla ) (227 scales), and giant ( Smutsia gigantea ) (1028 scales) pangolins. Haplotype diversity was higher for P. tricuspis scales (121 haplotypes, 66 novel) than that for P. tetradactyla (22 haplotypes, 15 novel) and S. gigantea (25 haplotypes, 21 novel) scales. Of the novel haplotypes, 74.2% were likely from western and west‐central Africa, suggesting potential resurgence of poaching and newly exploited populations in these regions. Our results illustrate the utility of extensively subsampling large seizures and outline an efficient molecular approach for rapid genetic screening that should be accessible to most forensic laboratories and enforcement agencies.

Temperature sensitivity of organic carbon decomposition in lake sediments is mediated by chemodiversity - Shuailong Wen; Ang Hu; Shuyu Jiang; Lei Han; Kyoung‐Soon Jang; Andrew J. Tanentzap; Jicheng Zhong; Jianjun Wang (Global Change Biology, 2024)
Organic carbon decomposition in lake sediments contributes substantially to the global carbon cycle and is strongly affected by temperature. However, the magnitude of temperature sensitivity ( Q 10 ) of decomposition and the underlying factors remain unclear at the continental scale. Carbon quality temperature (CQT) hypothesis asserts that less reactive and more recalcitrant molecules tend to have higher temperature sensitivities, but its support is challenged by complex composition of organic matter and environmental constraints. Here, we quantified Q 10 of the sediments across 50 freshwater ecosystems along a 3500 km north–south transect, and characterized the quality of sediment dissolved organic carbon with chemodiversity reflected in molecular richness, functional traits (i.e., molecular weight, bioavailability, etc.) and composition. We further included classic environmental variables, such as climatic, physicochemical and microbial factors, to explore how Q 10 is constrained by these factors or carbon quality. We found that Q 10 varied greatly across lakes, with the mean value of 1.78 ± 0.62, but showed nonsignificant latitudinal pattern. Q 10 was primarily predicted by chemodiversity and showed an increasing trend with the biochemical recalcitrance indicated by traits such as aromaticity and standard Gibb's Free Energy at both molecular and compositional levels. This suggests that carbon quality is the crucial determinant of Q 10 in lakes, supporting the CQT hypothesis. Moreover, Q 10 decreased linearly with the increase of molecular richness, implying that the resistance of decomposition to warming is associated with higher molecular diversity. Compared with the structural equation model containing only environmental variables, inclusion of chemodiversity increased 32.8% of the explained variation in Q 10 , and chemodiversity was the only driver showing direct effects. Collectively, this study illustrates the importance of chemodiversity in shaping the pattern of Q 10 , and has significant implications for accurately predicting the carbon turnover in lake ecosystems in the context of global warming.

Interdisciplinary methods for analysing food matrix structures of hybrid cell-based meats: A review - Olivia J. Ogilvie; Rachel Z. Bennie; Hamish J.F. Trlin; Larry Sai Weng Loo; Hanzhang Zhou; Ang Jin; Jin Kyo Oh; Renwick C.J. Dobson; Hanry Yu; Laura J. Domigan (Food Structure, 2024)

Correction: Geostatistical Rock Physics Inversion for Predicting the Spatial Distribution of Porosity and Saturation in the Critical Zone - Dario Grana; Andrew D. Parsekian; Brady A. Flinchum; Russell P. Callahan; Natalie Y. Smeltz; Ang Li; Jorden L. Hayes; Brad J. Carr; Kamini Singha; Clifford S. Riebe; W. Steven Holbrook (Mathematical Geosciences, 2022)

Geostatistical Rock Physics Inversion for Predicting the Spatial Distribution of Porosity and Saturation in the Critical Zone - Dario Grana; Andrew D. Parsekian; Brady A. Flinchum; Russell P. Callahan; Natalie Y. Smeltz; Ang Li; Jorden L. Hayes; Brad J. Carr; Kamini Singha; Clifford S. Riebe; W. Steven Holbrook (Mathematical Geosciences, 2022)

Cancer clinical trials in the Philippines - Michelle Ann B. Eala; Patricia Anne S. Basilio; Edward Christopher Dee; Reno Eufemon P. Cereno; Christian Daniel Ang; Nikko J. Magsanoc; Frederic Ivan L. Ting; Dennis L. Sacdalan (Cancer Causes & Control, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Microbial diversity of sub-bottom sediment cores from a tropical reef system - Ren Min Oh; Zheng Bin Randolph Quek; Yong Kit Samuel Chan; Ambert Chiam Foong Ang; Michael J. O’Leary; Danwei Huang; Benjamin J. Wainwright (Coral Reefs, 2022)

Latitudinal variation in growth and survival of juvenile corals in the West and South Pacific - Yoko Nozawa; Ronald D. Villanueva; Munasik Munasik; Kakaskasen Andreas Roeroe; Takuma Mezaki; Takashi Kawai; James Guest; Seiji Arakaki; Go Suzuki; Jean J. B. Tanangonan; Put O. Ang; Peter J. Edmunds (Coral Reefs, 2021)

Evidence of synergism among three genetic variants in a patient with LMNA-related lipodystrophy and amyotrophic lateral sclerosis leading to a remarkable nuclear phenotype - Kathryn Volkening; Sali M. K. Farhan; Jessica Kao; Cheryl Leystra-Lantz; Lee Cyn Ang; Adam McIntyre; Jian Wang; Robert A. Hegele; Michael J. Strong (Molecular and Cellular Biochemistry, 2021)
Neurodegenerative diseases, including amyotrophic lateral sclerosis (ALS), can be clinically heterogeneous which may be explained by the co-inheritance of multiple genetic variants that modify the clinical course. In this study we examine variants in three genes in a family with one individual presenting with ALS and lipodystrophy. Sequencing revealed a p.Gly602Ser variant in LMNA , and two additional variants, one each in SETX (g.intron10-13delCTT) and FUS (p.Gly167_Gly168del). These latter genes have been linked to ALS. All family members were genotyped and each variant, and each combination of variants detected, were functionally evaluated in vitro regarding effects on cell survival, expression patterns and cellular phenotype. Muscle biopsy retrieved from the individual with ALS showed leakage of chromatin from the nucleus, a phenotype that was recapitulated in vitro with expression of all three variants simultaneously. Individually expressed variants gave cellular phenotypes there were unremarkable. Interestingly the FUS variant appears to be protective against the effects of the SETX and the LMNA variants on cell viability and may indicate loss of interaction of FUS with SETX and/or R-loops. We conclude that these findings support genetic modifications as an explanation of the clinical heterogeneity observed in human disease.

Serotonin transporter protein in autopsied brain of chronic users of cocaine - Junchao Tong; Jeffrey H. Meyer; Isabelle Boileau; Lee-Cyn Ang; Paul J. Fletcher; Yoshiaki Furukawa; Stephen J. Kish (Psychopharmacology, 2020)

Vascular KATP channels protect from cardiac dysfunction and preserve cardiac metabolism during endotoxemia - Qadeer Aziz; Jianmin Chen; Amie J Moyes; Yiwen Li; Naomi A Anderson; Richard Ang; Dunja Aksentijevic; Sonia Sebastian; Adrian J Hobbs; Christoph Thiemermann; Andrew Tinker (Journal of Molecular Medicine, 2020)
K ATP channels in the vasculature composed of Kir6.1 regulate vascular tone and may contribute to the pathogenesis of endotoxemia. We used mice with cell-specific deletion of Kir6.1 in smooth muscle (smKO) and endothelium (eKO) to investigate this question. We found that smKO mice had a significant survival disadvantage compared with their littermate controls when treated with a sub-lethal dose of lipopolysaccharide (LPS). All cohorts of mice became hypotensive following bacterial LPS administration; however, mean arterial pressure in WT mice recovered to normal levels, whereas smKO struggled to overcome LPS-induced hypotension. In vivo and ex vivo investigations revealed pronounced cardiac dysfunction in LPS-treated smKO, but not in eKO mice. Similar results were observed in a cecal slurry injection model. Metabolomic profiling of hearts revealed significantly reduced levels of metabolites involved in redox/energetics, TCA cycle, lipid/fatty acid and amino acid metabolism. Vascular smooth muscle-localised K ATP channels have a critical role in the response to systemic infection by normalising cardiac function and haemodynamics through metabolic homeostasis. Key messages • Mice lacking vascular K ATP channels are more susceptible to death from infection. • Absence of smooth muscle K ATP channels depresses cardiac function during infection. • Cardiac dysfunction is accompanied by profound changes in cellular metabolites. • Findings from this study suggest a protective role for vascular K ATP channels in response to systemic infection.

Analysis of emission profiles from charcoal produced from selected tree species by different pyrolysis methods - T. J. Shikorire; G. O. Asudi; M. M. Ng’ang’a; G. Kirubi; A. Hassanali (International Journal of Environmental Science and Technology, 2019)

Critical Information Gaps Impeding Understanding of the Role of Larval Connectivity Among Coral Reef Islands in an Era of Global Change - Peter J. Edmunds; Shelby E. McIlroy; Mehdi Adjeroud; Put Ang; Jessica L. Bergman; Robert C. Carpenter; Mary A. Coffroth; Atsushi G. Fujimura; James L. Hench; Sally J. Holbrook; James J. Leichter; Soyoka Muko; et al. (Frontiers in Marine Science, 2018)

Horizontal and vertical distribution of sea lice larvae ( Lepeophtheirus salmonis ) in and around salmon farms in the Bay of Fundy, Canada - E J Nelson; S M C Robinson; N Feindel; A Sterling; A Byrne; K Pee Ang (Journal of Fish Diseases, 2018)
The sea louse, Lepeophtheirus salmonis , is parasitic to salmonid species in the Northern Hemisphere and has become a widespread biological and economic problem for the salmon farming industry. A better understanding is needed of their spatial distribution and early life history to disrupt the life cycle of the sea louse. In this study, sea lice larval densities within salmon farms, between salmon farms and reference sites, and at various depths were quantified using both plankton pumps and plankton nets. Farm sites exhibited significantly higher densities than reference sites; however, these densities dropped an order of magnitude at a distance of 100 m from the cages. The majority of the larvae captured in the study were nauplii (93%), and densities ranged from 0 to 10 larvae/m 3 . Free‐swimming sea lice larvae were found to exhibit a diel cycle where nauplii larvae were in deeper waters (10–17 m) during the day and in surface waters (1–6 m) during the night. The results of this study suggest that the early life‐history stages of sea lice originate from and may remain close to active salmon farms, creating a self‐sustaining population.

Oxoiron(IV) complexes as synthons for the assembly of heterobimetallic centers such as the Fe/Mn active site of Class Ic ribonucleotide reductases - Ang Zhou; Patrick M. Crossland; Apparao Draksharapu; Andrew J. Jasniewski; Scott T. Kleespies; Lawrence Que (JBIC Journal of Biological Inorganic Chemistry, 2018)

The actions of relaxin family peptides on signal transduction pathways activated by the relaxin family peptide receptor RXFP4 - Sheng Y. Ang; Dana S. Hutchinson; Bronwyn A. Evans; Mohammed A. Hossain; Nitin Patil; Ross A. D. Bathgate; Martina Kocan; Roger J. Summers (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Conservation of reef corals in the South China Sea based on species and evolutionary diversity - Danwei Huang; Bert W. Hoeksema; Yang Amri Affendi; Put O. Ang; Chaolun A. Chen; Hui Huang; David J. W. Lane; Wilfredo Y. Licuanan; Ouk Vibol; Si Tuan Vo; Thamasak Yeemin; Loke Ming Chou (Biodiversity and Conservation, 2016)

Diagnostic yield of repeat sampling with immunoassay, real-time PCR, and toxigenic culture for the detection of toxigenic Clostridium difficile in an epidemic and a non-epidemic setting - J. van Prehn; C. M. J. E. Vandenbroucke-Grauls; Y. H. van Beurden; R. van Houdt; S. Vainio; C. W. Ang (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Extraordinary diversity of reef corals in the South China Sea - Danwei Huang; Wilfredo Y. Licuanan; Bert W. Hoeksema; Chaolun Allen Chen; Put O. Ang; Hui Huang; David J. W. Lane; Si Tuan Vo; Zarinah Waheed; Yang Amri Affendi; Thamasak Yeemin; Loke Ming Chou (Marine Biodiversity, 2015)

A Head-to-Head Comparison of the Antimicrobial Activities of 30 Ultra-Short Antimicrobial Peptides Against Staphylococcus aureus, Pseudomonas aeruginosa and Candida albicans - Qiu Ying Lau; Xing Yao Choo; Zhi Xue Lim; Xin Ni Kong; Fui Mee Ng; Melgious J. Y. Ang; Jeffrey Hill; C. S. Brian Chia (International Journal of Peptide Research and Therapeutics, 2015)

Nitrogen Translocation to Fresh Litter in Northern Hardwood Forest - Ang Li; Timothy J. Fahey (Ecosystems, 2013)

Copper(II) ion removal from aqueous solutions using biosorption technology: thermodynamic and SEM–EDX studies - X. W. Ang; V. S. Sethu; J. M. Andresen; M. Sivakumar (Clean Technologies and Environmental Policy, 2013)

Filtration of sea louse, L epeophtheirus salmonis , copepodids by the blue mussel, M ytilus edulis , and the A tlantic sea scallop, P lacopecten magellanicus , under different flow, light and copepodid‐density regimes - A Bartsch; S M C Robinson; M Liutkus; K P Ang; J Webb; C M Pearce (Journal of Fish Diseases, 2013)
Population management of L epeophtheirus salmonis in C anada currently relies on chemotherapeutants to remove attached stages of the ectoparasite. However, some populations of L . salmonis are developing resistance to chemotherapeutants making alternate management measures necessary. This article explores the ability of filter‐feeding shellfish [ i.e . blue mussels ( Mytilus edulis ) and A tlantic sea scallops ( P lacopecten magellanicus )] to consume the copepodid stages of L . salmonis in the laboratory under static and flowing water conditions, with variable copepodid densities, and with the aid of a light attractant. M ytilus edulis consumed copepodids under both static and flowing water conditions, and the proportion of individuals ingested was similar at low and high copepodid densities, suggesting that M . edulis was not saturated at the concentrations tested. Also, M . edulis consumed more copepodids when a light attractant was present, suggesting that lights may be useful to concentrate widely dispersed copepodids around cultured shellfish in the field. Finally, P . magellanicus consumed the same number of copepodids as an equivalent total wet weight of M . edulis . During each of the four separate experiments, shellfish consumed between 18 and 38% of the copepodids presented per hour, suggesting that both species are well suited for low level removal of copepodids over time.

Characteristics of the smallholder free-range pig production system in western Kenya - John M. Kagira; Paul W. N. Kanyari; Ndicho Maingi; Samuel M. Githigia; J. C. Ng’ang’a; Julia W. Karuga (Tropical Animal Health and Production, 2010)

Human papillomavirus infection in women with and without cervical cancer in Nepal - Ang Tshering Lama Sherpa; Gary M. Clifford; Salvatore Vaccarella; Sadhina Shrestha; Mari Nygård; Balman Singh Karki; Peter J. F. Snijders; Chris J. L. M. Meijer; Silvia Franceschi (Cancer Causes & Control, 2010)

Structure and heterogeneity of gliadin: a hydrodynamic evaluation - Shirley Ang; Jana Kogulanathan; Gordon A. Morris; M. Samil Kök; Peter R. Shewry; Arthur S. Tatham; Gary G. Adams; Arthur J. Rowe; Stephen E. Harding (European Biophysics Journal, 2010)

The effects of anthelmintic treatments against gastrointestinal nematodes on the performance of breeding ewes and lambs on pasture in semi-arid Kenya - C. J. Ng’ang’a; N. Maingi; P. W. N. Kanyari; W. K. Munyua (Tropical Animal Health and Production, 2009)

Brain serotonin transporter in human methamphetamine users - Stephen J. Kish; Paul S. Fitzmaurice; Isabelle Boileau; Gregory A. Schmunk; Lee-Cyn Ang; Yoshiaki Furukawa; Li-Jan Chang; Dennis J. Wickham; Allan Sherwin; Junchao Tong (Psychopharmacology, 2009)

The effect of weather on the occurrence and magnitude of periparturient rise in trichostronglyid nematode egg output in Dorper ewes in a semi-arid area of Kajiado District of Kenya - C. J. Ng’ang’a; P. W. N. Kanyari; N. Maingi; W. K. Munyua (Tropical Animal Health and Production, 2006)

Wind protection in a hedged agroforestry system in semiarid Kenya - S. B. B. Oteng'i; C. J. Stigter; J. K. Ng'ang'a; D. N. Mungai (Agroforestry Systems, 2000)

Simply Obtained Global Radiation, Soil Temperature and SoilMoisture in an Alley Cropping System in Semi-Arid Kenya - D. N. Mungai; C. J. Stigter; C. L. Coulson; J. K. Ng'ang'a (Theoretical and Applied Climatology, 2000)

Warning colouration in pseudocerotid flatworms (Platyhelminthes, Polycladida). A preliminary study - Hing P. Ang; Leslie J. Newman (Hydrobiologia, 1998)

Use of egg custard augmented with cod liver oil and Moina micrura on production of freshwater prawn postlarvae - M. J. Alam; K. J. Ang; M. Begum (Aquaculture International, 1995)

Replacement of Artemia with Moina micrura in the rearing of freshwater shrimp larvae - M. J. Alam; K. J. Ang; M. Begum (Aquaculture International, 1995)